2009
DOI: 10.1158/0008-5472.can-09-0705
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Regulation and Suppression of Melanoma Invasiveness by Novel Retinoic Acid Receptor-γ Target Gene Carbohydrate Sulfotransferase 10

Abstract: Retinoic acid (RA) induces growth arrest and differentiation of S91 murine melanoma cells and serves as a valuable model for this disease. RA acts through activation of RA receptors (RAR), which are members of the nuclear receptor superfamily of ligand-inducible transcription factors. Interestingly, differentiation is mediated by RARγ, but not by RARα or RARβ, suggesting that RARγ possesses unique and uncharacterized molecular properties. To address this question, DNA microarrays in combination with RAR isofor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
(83 reference statements)
3
24
0
Order By: Relevance
“…Following treatment with 1 M RA, a marked increase of HNK-1ST mRNA was detected using RT-PCR (Fig. 1, A and B), consistent with a previous report (6). However, neither of the glucuronyltransferases (GlcAT-P and GlcAT-S) responsible for producing HNK-1 was observed (Fig.…”
Section: Specific Induction Of Hnk-1st Expression and Alternatesupporting
confidence: 90%
See 4 more Smart Citations
“…Following treatment with 1 M RA, a marked increase of HNK-1ST mRNA was detected using RT-PCR (Fig. 1, A and B), consistent with a previous report (6). However, neither of the glucuronyltransferases (GlcAT-P and GlcAT-S) responsible for producing HNK-1 was observed (Fig.…”
Section: Specific Induction Of Hnk-1st Expression and Alternatesupporting
confidence: 90%
“…Apparent confounding issues are that HNK-1ST functions as a tumor suppressor, although the resulting product, the HNK-1 epitope, promotes metastasis. However, it should be noted that whereas Zhao et al (6) reported that HNK-1ST functions as a tumor suppressor, they failed to detect the HNK-1 epitope in 56 primary and 20 metastatic melanomas. This means that HNK-1ST might regulate invasiveness through an HNK-1 epitope-independent pathway.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations